FAKTOR-FAKTOR YANG MEMPENGARUH TERHADAP TINGKAT DEPOSIT BANK UMUM SYARIAH PERIODE 2011-2018 - Sri Fatimah Luliansari; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of partial and simultaneous variables of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Deposit Insurance System (DIS) on Deposit Rates of Islamic commercial banks in the 2011-2018 period. The data used in this study are secondary data from the Financial Services Authority Report and Sharia Banking Annual Report 2010-2018. The analytical method used in this study is the penel data regression analysis test, where the sample used amounted to 11 Islamic commercial banks obtained by purposive sampling method. The results of the analysis of the best model data used by the author are the Fixed Effect Model. On the results of this researchers simultaneously all variables affect the level of Islamic commercial bank deposits. But partially the CAR and NPF variables have a positive effect on the deposit rate while the DIS does not affect the deposit rate.Keywords: Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Deposit Insurance system (DIS), Tingkat Deposit